Almost Periodic Functions and Their Applications: A Survey of Results and Perspectives - Wei-Shih Du; Marko Kostić; Manuel Pinto (Journal of Mathematics)
The main aim of this survey article is to present several known results about vector-valued almost periodic functions and their applications. We separately consider almost periodic functions depending on one real variable and almost periodic functions depending on two or more real variables. We address several open problems and possibilities for further investigations of almost periodic functions, quoting more than two hundred references about the subject under our consideration.